Comparison of the Seattle Heart Failure Model and Cardiopulmonary Exercise Capacity for Prediction of Death in Patients With Chronic Ischemic Heart Failure and Intracoronary Progenitor Cell Application. Issue 3 (3rd February 2013) - Honold, Joerg; DeRosa, Salvatore; Spyridopoulos, Ioakim; Fischer‐Rasokat, Ulrich; Seeger, Florian H.; Leistner, David; Lotz, Saskia; Levy, Wayne C.; Zeiher, Andreas M.; Assmus, Birgit
Abstract Background: Despite many therapeutic advances, the prognosis of patients with chronic heart failure (CHF) remains poor. Therefore, reliable identification of high‐risk patients with poor prognosis is of utmost importance. Cardiopulmonary exercise testing (CPET) provides important prognostic information by peak O2 uptake (peak VO2), maximal oxygen pulse (O2 Pmax), O2 uptake efficiency slope (OUES), and VE/VCO2 slope (VE/VCO2). A different approach for prognostic assessment is the Seattle Heart Failure Model (SHFM), which is based on clinical data and calculates the estimated annual mortality. Hypothesis: Comparison of the prognostic value of the Seattle Heart Failure Score and cardiopulmonary excercis testing in patients with chronic heart failure. Methods: One hundred fifty‐seven patients with ischemic heart failure and recent intracoronary progenitor cell application were analyzed for mortality during a follow‐up of 4 years. CPET (peak VO2, O2 Pmax, OUES, VE/VCO2) was performed in all patients at baseline. The SHFM score was calculated for every patient, with data obtained at the time of CPET. Results: During follow‐up, 24 patients died (15.2%). Nonsurvivors had significantly worse initial CPET results and a higher SHFM score compared to survivors. Receiver operating characteristics curve analysis of sensitivity and specificity revealed the largest area under the curve value for the SHFM score, followed by VE/VCO2 slope. Kaplan Meier analysis using cutoff points of SHFM and VE/VCO2 slope with highest sensitivity and specificity resulted in significant discrimination of survivors and nonsurvivors. By multivariate analysis, only the SHFM score persisted as independent predictor of mortality in these patients. Conclusions: These data indicate superior prognostic power of the SHFM score compared to CPET in patients with chronic ischemic heart failure. The authors have no funding, financial relationships, or conflicts of interest to disclose.